The immunomodulation–immunogenicity balance of equine Mesenchymal Stem Cells (MSCs) is differentially affected by the immune cell response depending on inflammatory licensing and major histocompatibility complex (MHC) compatibility - Cequier, Alina; Vázquez, Francisco José; Romero, Antonio; Vitoria, Arantza; Bernad, Elvira; García-Martínez, Mirta; Gascón, Isabel; Barrachina, Laura; Rodellar, Clementina (Frontiers in Veterinary Science, 2022)
The immunomodulatory properties of equine mesenchymal stem cells (MSCs) are important for their therapeutic potential and to escape from immune recognition, which may also be influenced by donor-recipient major histocompatibility complex (MHC)-matching/mismatching and MHC expression level. Factors such as inflammation can modify the balance between regulatory and immunogenic profiles of equine MSCs, but little is known about how the exposure to the immune system can affect these properties in equine MSCs. In this study, we analyzed the gene expression and secretion of molecules related to the immunomodulation and immunogenicity of equine MSCs, either non-manipulated (MSC-naïve) or stimulated by pro-inflammatory cytokines (MSC-primed), before and after their exposure to autologous or allogeneic MHC-matched/mismatched lymphocytes, either activated or resting. Cytokine priming induced the immunomodulatory profile of MSCs at the baseline (MSCs cultured alone), and the exposure to activated lymphocytes further increased the expression of interleukin 6 (IL6), Cyclooxygenase 2 and inducible nitric oxide synthase, and the IL6 secretion. Activated lymphocytes were also able to upregulate the regulatory profile of MSC-naïve to levels comparable to the cytokine priming. On the contrary, resting lymphocytes did not upregulate the immunomodulatory profile of equine MSCs but, interestingly, MSC-primed exposed to MHC-mismatched lymphocytes showed the highest expression and secretion of these mediators, which may be potentially linked to the activation of lymphocytes upon recognition of foreign MHC molecules. Cytokine priming alone did not upregulate the immunogenic genes, but MSC-primed exposed to activated or resting lymphocytes increased their MHC-I and MHC-II expression regardless of the MHC-compatibility. The upregulation of immunogenic markers including CD40 in the MHC-mismatched co-culture might have activated lymphocytes which, at the same time, could have promoted the immune regulatory profile aforementioned. In conclusion, activated lymphocytes are able to induce equine MSC regulatory profile and their effects seem to be additive to the priming action. Importantly, our results suggest that the lymphocyte response against MHC-mismatched MSC-primed would promote further activation of their immunomodulatory ability, which eventually might help them to evade this reaction. Further studies are needed to clarify how these findings might have clinical implications in vivo, which will help developing safer and more effective therapies.